The knowledge and attitudes of field hockey athletes to injury, injury reporting and injury prevention: A qualitative study - Rees, H.; Matthews, J.; McCarthy Persson, U.; Delahunt, E.; Boreham, C.; Blake, C. (Journal of Science and Medicine in Sport, 2022)
Objectives: Researchers have often struggled to successfully implement injury prevention strategies in real-world practice. This is despite such strategies proving successful in reducing overall injury incidence and burden. It has been hypothesised that this may be because the behavioural and contextual factors related to sports injury are not fully understood. Such factors stem from multiple key stakeholders, including the athlete. The primary aim of this study was to investigate athletes' knowledge and attitudes towards injury, injury reporting and prevention, as well as some of the barriers that may impact the future implementation of prevention strategies. Design: Qualitative; with semi-structured interviews following an interpretivist approach. Methods: Twenty-two field hockey athletes, playing in the top-tier Irish Hockey League were interviewed. Data were analysed using reflexive thematic analysis, with three general dimensions containing six higher-order themes. Results: The findings highlighted that athletes have a varied understanding of injury, which tends to improve with experience. The reporting of injuries by athletes to members of the coaching staff was relatively poor. This may be due to limited resources and supports available to athletes which also cause challenges to injury prevention. Conclusions: Future injury prevention strategies in field hockey need to account for athletes' varied understanding of what constitutes an injury. Furthermore, policy changes to influence potential barriers to injury may assist in preventing or reducing the number of injuries being sustained by athletes.